Practice-Oriented Approach in the System of Professional Training of Future Teachers to Social-Pedagogical Activity - Budnyk, Olena (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The article highlights theoretical aspects of the socio-pedagogical direction of pedagogical practice of future primary school teachers.The tasks of pedagogical practice as a mandatory component of professional training of future specialists are outlined. The necessity of involvement employers in cooperation with higher education institutions to ensure a high level of continuous practical training, creating conditions for professional development and self-realization of future teachers are substantiated. Great emphasis is placed on the need for creative use of theoretical knowledge and practical skills working with students, modern teaching technologies, students’ educational and social development, as well as systematic professional self-improvement and self-development. It was proved that in the process of teacher training system pedagogical practice performs a number of important functions: educational, developmental, diagnostic and corrective, communicative, organizational (management), prognostic, preventive, etc. The approximate content of this student practice in general educational institutions is given taking into account such directions, as: work with deviant and gifted pupils, inclusive education, sociocultural animation, etc. The results of an empirical study on the readiness of graduates of pedagogical specialties for the practical use of social and educational technologies in school are presented. The difficulties most often faced by respondents in working with students were identified, including: work with different categories of parents, individual counseling of students, resolution of pedagogical conflicts, implementation of diagnostic activities and socio-pedagogical communication, etc. The author proved that combination of theoretical and practical teacher training, integration of teaching with research and experimental work would contribute to the practical orientation of the educational process at the university, active search and implementation of non-traditional forms and methods of teaching, in particular in socio-pedagogical aspects. The article partially uses the materials of the author's dissertation “Theoretical and methodological principles of professional training of future primary school teachers for socio-pedagogical activities” (2015) for the degree of Doctor of Pedagogical Sciences.